115k views
2 votes
Which expression is equivalent to 17x − 8x + 2 and why?

2 − 9x, because (17x − 8x) + 2 = −9x + 2 = 2 − 9x
2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x
11x, because 17x − 8x + 2 = 9x + 2 = 11x
7x, because 17x − 8x + 2 = 17x − 10x = 7x

2 Answers

1 vote

Answer:

2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x

Explanation:

17x - 8x + 2 = (17x - 8x) +2

Combine like terms.

= 9x + 2 Like terms have same variable of same powers.

Still stuck? Get 1-on-1 help from an expert tutor now.e3radg8 and 3 more users found this answer helpful

User Marbel
by
5.2k points
4 votes

Answer:

2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x

Explanation:

17x - 8x + 2 = (17x - 8x) +2 Combine like terms.

= 9x + 2

Like terms have same variable of same powers.

User Juffy
by
5.6k points